Enculturation of Islamic Education Values for Children with Special Needs - Sri Widyastri; Isman Iskandar; Nila Murtadhiyah Hakim; Windy Ajeng Kartini; Haneen Mustafa Milad Muhaireth (FKIP Universitas Halu Oleo, 2023)
Children with special needs have equal rights in accessing and practicing Islamic religious values in schools. Islamic values need to be enculturated from generation to generation regardless of differences in student backgrounds. But in reality, children with special needs do not have the ability to think and understand well the Islamic material taught by their teachers. This paper wants to analyze the process of enculturation of the values of Islamic education in children with special needs at the Nur Asih Special School. To study this problem, researchers use the theory of enculturation. The research method is descriptive qualitative with observation techniques, interviews, and documentation. The research findings show that the inheritance of Islamic educational values such as the values of monotheism, worship, and morals occurs through a process of enculturation within the Nur Asih Special school environment. Several stages of enculturation occurred at the Nur Asih Special School, namely the process of introducing Islamic values through audio-visual, the process of imitation as well as the process of training and coaching. The process of enculturation occurs formally, especially on Fridays. Children with special needs at the Nur Asih Special School have delayed intelligence functions and face obstacles in the learning process. The process of enculturation of Islamic values also experienced delays in students with special needs children at Nur Asih School compared to normal children in general.